PTFE Content in Catalyst Layers and Microporous Layers: Effect on Performance and Water Distribution in Polymer Electrolyte Membrane Fuel Cells. Issue 3 (16th March 2021) - Mohseninia, A.; Eppler, M.; Kartouzian, D.; Markötter, H.; Kardjilov, N.; Wilhelm, F.; Scholta, J.; Manke, I.
Abstract : This work describes the effects of catalyst layers (CLs) consisting of hydrophobic PTFE on the performance and water management of PEM fuel cells. Catalyst inks with various PTFE contents were coated on Nafion membranes and characterized using contact angle measurements, SEX-EDX, and mercury porosimetry. Fuel cell tests and electrochemical impedance spectroscopy (EIS) were conducted under varying operating conditions for the prepared materials. At dry conditions, CLs with 5 wt.% PTFE were advantageous for cell performance due to improved membrane hydration, whereas under humid conditions and high air flow rates CLs with 10 wt.% PTFE improved the performance in high current density region. Higher PTFE contents (≥20 wt.%) increased the mass transport resistance due to reduced porosity of the CLs structure. Operando neutron radiography was utilized to study the effects of hydrophobicity gradients within CLs and cathode microporous layer (MPLC ) on liquid water distribution. More hydrophobic CLs increased the water content in adjacent layers and improved performance, especially at dry conditions. MPLC with higher PTFE contents increased the overall liquid water within the CLs and GDLs and escalated the water transfer to the anode side. Furthermore, the role of back-diffusion transport mechanism on water distribution was identified for the investigated cells.